MicroRNA biomarkers in leprosy: insights from the Northern Brazilian Amazon population and their implications in disease immune-physiopathology - Cáceres-Durán, Miguel Ángel; Pinto, Pablo; Magalhães, Leandro; de Souza, Tatiane Piedade; Gobbo, Angelica; Barreto, Josafá Gonçalves; da Silva, Moises Batista; Fagundes da Costa, Patrícia; Salgado, Claudio Guedes; Ribeiro-dos-Santos, Ândrea (Frontiers in Genetics, 2024)
Leprosy, or Hansen’s Disease, is a chronic infectious disease caused by Mycobacterium leprae that affects millions of people worldwide. Despite persistent efforts to combat it leprosy remains a significant public health concern particularly in developing countries. The underlying pathophysiology of the disease is not yet fully understood hindering the development of effective treatment strategies. However, recent studies have shed light on the potential role of microRNAs (miRNAs), small non-coding RNA molecules that can regulate gene expression, as promising biomarkers in various disease, including leprosy. This study aimed to validate a set of nine circulating miRNAs to propose new biomarkers for early diagnosis of the disease. Hsa-miR-16-5p, hsa-miR-106b-5p, hsa-miR-1291, hsa-miR-144-5p, and hsa-miR-20a-5p showed significant differential expression between non-leprosy group (non-LP) and leprosy group (LP), accurately discriminating between them (AUC > 0.75). In addition, our study revealed gender-based differences in miRNA expression in LP. Notably, hsa-miR-1291 showed higher expression in male LP, suggesting its potential as a male-specific biomarker. Similarly, hsa-miR-16-5p and hsa-miR-20a-5p displayed elevated expression in female LP, indicating their potential as female-specific biomarkers. Additionally, several studied miRNAs are involved in the dysregulation of apoptosis, autophagy, mitophagy, cell cycle, and immune system in leprosy. In conclusion, the validation of miRNA expression highlights several miRNAs as potential biomarkers for early diagnosis and provides new insights into the pathogenesis of the disease.